TEACHER MOTIVATION AND STIMULATION IN HIGHER EDUCATION INSTITUTIONS OF RUSSIA: CURRENT STATE, EXPERIENCE, PROBLEMS, SEARCH FOR NEW MODELS - Urzha, Olga; Makushkin, Sergei (Revista Inclusiones, 2020)
The quality of education and its effectiveness are largely determined by the qualities of those who teach, the people who conduct the educational process. This article discusses the factors that determine the quality of teaching staff in higher education institutions. It analyzes the environmental conditions that determine teachers’ attitudes and affect motivation in professional activity at present and further compares it with other historical periods when the conditions in the field were different from the current ones.